The influence of hydrogen on Lomer junctions. (June 2019) - Yu, Haiyang; Cocks, Alan C.F.; Tarleton, Edmund
Abstract: The influence of hydrogen on Lomer junctions is studied using three dimensional discrete dislocation plasticity simulations which incorporate the hydrogen elastic stress field. Hydrogen can either increase or decrease the junction length, depending on the initial dislocation configuration. However, hydrogen reduces the strength of these junctions, since the Peach-Koehler forces generated by the hydrogen elastic stress field always promote the conversion of a Lomer junction into a Frank-Read source. A microcantilever bend test containing Lomer junctions is simulated showing hydrogen softens the global load-displacement curve, which is partly due to the junction weakening effect revealed here. Graphical abstract: Unlabelled Image